A four-legs matrix converter ground power unit with repetitive voltage control - Rohuma, Wesam; Zanchetta, Pericle; Wheeler, Patrick; Empringham, Lee (Institute of Electrical and Electronics Engineers, 2015)
In this paper, a four-leg matrix converter is proposed as the power conversion core for aircraft ground power unit (GPU) applications. This structure allows easy management of unbalanced and nonlinear loads with minimal disruption of the power supply operation. A hybrid repetitive-traditional control system is proposed to regulate the output voltage of the GPU. This solution reduces the steady-state tracking error, maintaining fast dynamic characteristics, and increases the stability of the converter compared to conventional approaches. Simulations and experimental results from a 7.5-KW converter prototype are presented to verify the operation of the proposed configuration and to prove the effectiveness of the solution.